PERAN JOB SATISFACTION DALAM MEMEDIASI HUBUNGAN TRANSFORMATIONAL LEADERSHIP, SELF EFFICACY, DAN INNOVATIVE WORK BEHAVIOR PADA PEGAWAI DINAS PERTANIAN KOTA PAYAKUMBUH - Susi Suheni; Heliyani (Journal Publicuho, 2025)
This study aims to examine the influence of transformational leadership and self-efficacy on innovative work behaviour mediated by job satisfaction. A quantitative approach with hypothesis testing techniques was used in this study. 73 samples were used using a saturated sampling technique, namely, all employees of the Payakumbuh City Agriculture Office. Data were collected through offline questionnaire distribution and processed using SmartPLS 4.0 software with structural equation modelling techniques. The results showed that transformational leadership and self-efficacy each had a positive and significant effect on job satisfaction. Transformational leadership, self-efficacy, and job satisfaction each have a positive and significant influence on innovative work behaviour. The influence of transformational leadership and self-efficacy on innovative work behaviour through the mediation of job satisfaction was found to be positive and significant. The implications of this study emphasise the importance of meeting the needs and comfort of employees in government agencies in order to foster innovative work behaviour.